ON EUROPEAN UNION ECONOMIC GROWTH: IS COHESION POLICY STILL RELEVANT? - Cătălin Marian COSTACHE; Marcel Ioan BOLOȘ (Annals of the University of Oradea: Economic Science)
The geostrategic and macroeconomic landscaped is quickly changing and, lately at a faster pace. The European Union is faced with many challenges and has to find appropriate instruments to address them. Cohesion policy was a staple of EU instruments addressing regional disparities by supporting competitiveness, human capital and territorial cohesion and quality of life. The fields of intervention of the cohesion policy have increased over time and have diversified in a multitude of objectives and programs diluting its resources. But new circumstances require new approaches. NextGenerationEU RRF has risen to be an adapted instrument to a multitude of crises with a performance mechanism that sees reforms performed at the same time with investments. In this article we analyse the concepts, macroeconomic neoclassical theory and empiric results a show that there is still an important role for the Cohesion policy especially in increasing the efficiency factors in the neoclassical production functions which would ensure and advancement in the growth of the EU economy while also allowing for cohesion “the glue that keeps Europe together”.